PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS E-GAMES EDUKATIF WORDWALL TERHADAP KEMAMPUAN MATEMATIKA ANAK USIA 5-6 TAHUN - Rahmi, Ulfa; Yaswinda, Yaswinda; Mahyuddin, Nenny; Zulminiati, Zulminiati (Universitas Muhammadiyah Metro, 2025)
The lack of mathematical skills in children that include classifying, measuring, adding requires teachers to be more creative in creating fun, interesting, and interactive learning to increase children's interest and understanding. This study aims to examine whether there is an effect of implementing interactive learning media based on educational e-games wordwall on the mathematical abilities of children aged 5-6 years at Aisyiyah I Kindergarten Bukittinggi. This study is included in the type of quasi-experimental approach. The population used was all children at Aisyiyah I Kindergarten Bukittinggi in the 2024/2025 academic year, to determine the sample using a purposive sampling technique, for children in class B1 determined to be the control class, and class B4 as the experimental class. The data processing method in this study uses normality, homogeneity, and hypothesis testing. The data collection instrument uses a statement sheet. Then the data is analyzed using a difference test (t-test) using SPSS 27 statistical software. Referring to the results of observations that have been carried out, the mathematical abilities of children aged 5-6 years in the experimental class using interactive learning media based on educational e-games wordwall are greater than the control class. In the pre-test, the experimental class obtained a mean of 19.2 and the control class 17, while for the post-test in the experimental class, the mean was 30 and the control class 23. The sig value (2-tailed) shows a figure of 0.000 <0.05. There is a difference in the results after the intervention was given to both classes. There was a significant increase in the experimental class. While the control class also experienced an increase, but it was not significant. These findings indicate that the use of interactive wordwall learning media has a significant influence on the mathematical abilities of children aged 5-6 years.